PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT VANIA INTERIOR FURNISHINGS JAKARTA SELATAN - Syahdan Aziz, Firzie; Sulistiani, Sinta (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to find the effect of work discipline and physical work environment on employee performance at PT. Vania Interior Furnishings South Jakarta, both partially and simultaneously. The method used is a quantitative method. The sampling technique used is saturated sampling using a sample of 70 respondents. Data analysis using validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, determination coefficient analysis and hypothesis test. The results of this study are that work discipline has a significant effect on employee performance based on the hypothesis test obtained with Tcount> Ttable (10.136> 1.667), ρ value <Sig.0.05 or (0.000 <0.05) which means H0 is rejected and H1 is accepted and H2 is accepted. The regression equation value Y = 10.441 and X1 is 0.702, the coefficient value obtained is 0.776 meaning that the two variables have a positive and strong relationship. The determination value or contribution of its influence is 0.596 or 59.6%. The physical work environment has a significant effect on employee performance based on the hypothesis test obtained with a Tcount value > Ttable (11,688 > 1.667), ρ value < Sig.0.05 or (0.000 < 0.05) which means H0 is rejected and H2 is accepted and obtained H0 is rejected. The value of the regression equation Y = -4.611 and X2 = 1.085, the correlation coefficient value of 0.817 means that the two variables have a positive and strong relationship level. The determination value or contribution of its influence is 0.663 or 66.3%. Work discipline and work environment simultaneously have a significant effect on employee performance based on the hypothesis test obtained with a Fcount value > Ftable or (97,806 > 3.13,) ρ value < Sig.0.05 or (0.000 < 0.05) which means H0. rejected and H3 is accepted and the regression equation value is obtained Y = -1.835, X1 = 0.464, X2 = 0.557. The correlation coefficient value or the level of relationship between the independent variable and the dependent variable is 0.863, meaning that it has a positive level of relationship with a perfect correlation degree. The determination value or contribution of its influence is 0.737 or 73.7%.